Methods of Predicting the Heading, Pitch and Roll Angles for an Unmanned Aerial Vehicle - Damian Wierzbicki; Kamil Krasuski (Communications - Scientific letters of the University of Zilina, 2020)
The article discusses handicaps in predicting values of rotation angles with regard to Heading, Pitch and Roll for an Unmanned Aerial Vehicle. Within the simulation of the rotation angle values, the linear, polynomial and logarithmic methods were used. The programme source code was written in the numerical editor Scilab 5.4.1. The source data for investigation were recorded by a measuring device Trimble UX-5. The article provides results of comparing the real values of Heading, Pitch and Roll rotation angles to findings obtained from the prediction methods. Based on the conducted research, it was found that the largest value of standard deviation parameter in prediction of the rotation angles is for the angle of Heading, as it equals approximately 5o, whereas the smallest ones are for the Roll and Pitch angles, equalling less than 1.4o.